Intermedialny potencjał Arwa Stanisława Czycza - Marecki, Piotr (Slavia Occidentalis, 2011)
The article discusses a text hybrid, which is Arw by Stanisław Czycz, published in 2007, a literary work spread formally and thematically between such disciplines as literature, music, visual arts and textology. The author of the paper submits a thesis that this text is ideal to be read by means of intermedial tools. The author views Czycz’s work as precursory to the modern medial literary forms that originated along with the development of the Internet network. The article also presents how the book originated as a screenplay for Andrzej Wajda’s film dedicated to Andrzej Wróblewski.